Pan-Cancer Analysis of Genomic and Prognostic Characteristics Associated With Coronavirus Disease 2019 Regulators - Zhang, Jian; Jiang, Huali; Du, Kunpeng; Xie, Tao; Wang, Baiyao; Chen, Chengcong; Cen, Bohong; Yuan, Yawei; Ye, Jiacai (Frontiers in Medicine, 2021)
Background: Cancer patients are alleged to have poor coronavirus disease 2019 (COVID-19) outcomes. However, no systematic or comprehensive analyses of the role and mechanisms of COVID-19 receptor-related regulators in cancer are available. Methods: We comprehensively evaluated the genomic alterations and their clinical relevance of six COVID-19 receptor-related regulators (transmembrane serine protease 2 (TMPRSS2), angiotensinogen (AGT), angiotensin-converting enzyme 1 (ACE1), solute carrier family 6 member 19 (SLC6A19), angiotensin-converting enzyme 2 (ACE2), and angiotensin II receptor type 2 (AGTR2) across a broad spectrum of solid tumors. RNA-seq data, single nucleotide variation data, copy number variation data, methylation data, and miRNA-mRNA interaction network data from The Cancer Genome Atlas (TCGA) of 33 solid tumors were analyzed. We assessed the sensitivities of drugs targeting COVID-19 receptor-related regulators, using information from the Cancer Therapeutics Response Portal database. Results: We found that there are widespread genetic alterations of COVID-19 regulators and that their expression levels were significantly correlated with the activity of cancer hallmark-related pathways. Moreover, COVID-19 receptor-related regulators may be able to be used as prognostic biomarkers. By mining the genomics of drug sensitivities in cancer databases, we discovered a number of potential drugs that may target COVID-19 receptor-related regulators. Conclusion: This study revealed the genomic alterations and clinical characteristics of COVID-19 receptor-related regulators across 33 cancers, which may clarify the potential mechanism between COVID-19 receptor-related regulators and tumorigenesis and provide a novel approach for cancer treatments.